Identification of molecular pattern and prognostic risk model based on ligand-receptor pairs in liver cancer - Hu, Pengbo; Xu, Liang; Liu, Yongqing; Zhang, Xiuyuan; Li, Zhou; Li, Yiming; Qiu, Hong (Frontiers in Immunology, 2023)
The tumor microenvironment of hepatocellular carcinoma is composed of multiple cells, and the interactive communication between cells drives tumor progression and characterizes the tumor. Communication between cells is mainly achieved through signal transduction between receptor ligands, and the rise of single-cell technology has made it possible to analyze the communication network between cells. In this experiment, we analyzed the composition of the microenvironment of liver cancer by combining single-cell sequencing data and transcriptome sequencing data from liver cancer, and found that liver cancer tissues are rich in immune and mesenchymal cells, and there is extensive signaling between individual cells, so we constructed molecular typing and risk models for LRs. Combining clinical data revealed significant differences in clinical characteristics and prognosis between the molecular typing of receptor-ligand pairs, as well as in sensitivity to drugs; similarly, there were significant prognostic differences between the risk models. There were also notable differences in mutated genes, activated signaling pathways, infiltrating immune cells and immune subtypes. Subsequently, we used siRNA to knock down SLC1A5 in hepatocellular carcinoma cells and found that cell proliferation, migration and invasion were diminished. Meanwhile, we also performed polarization of macrophages. In conclusion, our LRs model may become a marker to guide clinical treatment and prognosis.